Answers

2014-07-06T11:51:30+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
So we know that for quadratic equation ax² +bx +c = 0
whose roots are m,n we know that x² - ( m + n)x +mn = 0 the previous quadratic equation
we know sum of roots = -b/a
product of roots = c/a
so in this sum
roots of the equation are 4x² +7x + 2 = 0
                  α +β  = -7/4
                    αβ = 2/4 = 1/2
 so to form the quadratic equation as given above using x² - ( m + n)x +mn = 0
so x² - ( α² + β² )x + (αβ)² = 0
so using formula a² +b² = (a +b)² - 2ab

so x² - ( α² + β² )x + (αβ)² = 0

⇒x² - {(α+ β)² - 2αβ }x + (αβ)² = 0
⇒x² - {(-7/2)² - 2 ×1/2}x + (1/2)² = 0
⇒4x²  - 49x + 1 = 0
so the required quadratic equation is 

4x²  - 49x + 1 = 0




                                  
0